Aging and Alcohol Interact to Alter Hepatic DNA Hydroxymethylation. (28th July 2014) - Tammen, Stephanie A.; Dolnikowski, Gregory G.; Ausman, Lynne M.; Liu, Zhenhua; Sauer, Julia; Friso, Simonetta; Choi, Sang‐Woon
<x xml:space="preserve">Abstract</x> Background Aging and chronic alcohol consumption are both modifiers of DNA methylation, but it is not yet known whether chronic alcohol consumption also alters DNA hydroxymethylation, a newly discovered epigenetic mark produced by oxidation of methylcytosine. Furthermore, it has not been tested whether aging and alcohol interact to modify this epigenetic phenomenon, thereby having an independent effect on gene expression. Methods Old (18 months) and young (4 months) male C57BL/6 mice were pair‐fed either a Lieber‐DeCarli liquid diet with alcohol (18% of energy) or an isocaloric Lieber‐DeCarli control diet for 5 weeks. Global DNA hydroxymethylation and DNA methylation were analyzed from hepatic DNA using a new liquid chromatography‐tandem mass spectrometry method. Hepatic mRNA expression of the Tet enzymes were measured via quantitative real‐time polymerase chain reaction. Results In young mice, mild chronic alcohol exposure significantly reduced global DNA hydroxymethylation compared with control mice (0.22 ± 0.01 vs. 0.29 ± 0.06%, p = 0.004). Alcohol did not significantly alter hydroxymethylcytosine levels in old mice. Old mice fed the control diet showed decreased global DNA hydroxymethylation compared with young mice fed the control diet (0.24 ± 0.02 vs. 0.29 ± 0.06%, p = 0.04). This model suggests an interaction between aging and alcohol in determining DNA hydroxymethylation (pinteraction = 0.009). Expression of Tet2 and Tet3 was decreased in the old mice relative to the young (p < 0.005). Conclusions The observation that alcohol alters DNA hydroxymethylation indicates a new epigenetic effect of alcohol. This is the first study demonstrating the interactive effects of chronic alcohol consumption and aging on DNA hydroxymethylation.